Philosophy and Legal Principles of 'Adam Al-Gharar Bai' Al-Salam And its Embodiments in Online Transactions - Cipta Lukmanul Hakim (UIN Sunan Gunung Djati Bandung, 2023)
This article explains the philosophy and legal principles of 'adam al-gharar bai' al-salam contract practiced by modern society. In contemporary economic practice, the bai' al-salam contract is widely used in online transactions. The existence of online transactions removes regional boundaries in transactions so that sellers and buyers do not need to meet. Online transactions raise various new problems such as; non-compliance with the specifications of the product ordered, quantity that does not match the order, quality that does not match the order, until there is uncertainty of accountability in the event of damage to the product. The methodology of this article uses a literature study with descriptive analysis. Data were obtained from various books, journals and other online sources. The results of the study show that the philosophy and principles contained in bai' al-salam are mutual help, certainty, and justice. As for the practice of online transactions, the legal principle of 'adam al-gharar bai' as-salam can be applied as long as the seller lists and describes the size, quality of the product or its constituent materials on its online platform